A grounded theory approach to understand the Portuguese emerging adult self-initiated expatriates' cross-cultural adaptation in the United Kingdom. Issue 1 (15th April 2019) - Farcas, Diana; Gonçalves, Marta
Abstract : Purpose: The purpose of this paper is to inductively develop a model of cross-cultural adaptation for emerging adult self-initiated expatriates (SIEs). Design/methodology/approach: Data were collected through semi-structured interviews with 18 Portuguese emerging adult SIEs, aged between 18 and 29 years, residing in the UK from 5 months to 2 years. The analysis of these interviews through a grounded theory, using computer-assisted qualitative data analysis software (Atlas.ti), allowed describing what constitutes participants' cross-cultural adaptation and what are its determinants. Findings: Five dimensions of cross-cultural adaptation emerged (cultural, emotional, social, practical and work), along with 18 determinants related with four different levels: personal, interpersonal, societal and situational. These determinants are related with the pre- and post-relocation phases of participants' expatriation experience and some of them act as buffers, capturing a more integrative picture of the cross-cultural adaption process. Research limitations/implications: In order to enhance the validity of the inductively identified relationships between cross-cultural adaptation and its determinants, the authors consider that they could be empirically tested. Originality/value: This study points to several contributions in the fields of cross-cultural adaptation, emerging adulthood and self-initiated expatriation. By considering this study's sample, the authors contributed to Farcas and Gonçalves' (2016) call for more research focusing on emerging adult SIEs. In doing so, the authors simultaneously addressed the gap in the emerging adulthood literature regarding the focus on non-university samples of emerging adults. The methodology of this study can also be considered a contribution. By conducting interviews with emerging adult SIEs and analyzing them through a grounded theory approach, the authors were able to develop a model of cross-cultural adaptation. To the best of the authors' knowledge, this is the first model which was inductively developed, enabling a broad understanding of emerging adult SIEs' cross-cultural adaptation, in terms of what constitutes and influences it.